Earmuff Noise Leakage Measurements and Evaluation - GERGES, Samir Nagi Yousri; GERGES, Rafael Nagi Cruz; DIAS, Roberto Alexandre (Archives of Acoustics, 2015)
This paper reports the quantitative effect of leakage on the noise attenuation of earmuff hearing protectors. The technology used in this study to measure the noise leakage is considered to be a new contribution to this topic. An array of sensors placed between an earmuff and a dummy human head or flat surface was used to measure the contact area. Areas of no contact are considered as the leakage elements. Eight earmuffs varying from high quality/high cost to low quality/low cost were tested, the leakage areas were measured and the reduction in the noise attenuation due to leakage was calculated.